Moon Witch, Spider King : The Dark Star Trilogy #2 - James, Marlon, 1970- (New York : Riverhead Books, 2022)
"From Marlon James, author of the bestselling National Book Award finalist Black Leopard, Red Wolf, the second book in the Dark Star trilogy, his African Game of Thrones. In Black Leopard, Red Wolf, Sogolon the Moon Witch proved a worthy adversary to Tracker as they clashed across a mythical African landscape in search of a mysterious boy who disappeared. In Moon Witch, Spider King, Sogolon takes center stage and gives her own account of what happened to the boy, and how she plotted and fought, triumphed and failed as she looked for him. It's also the story of a century-long feud-seen through the eyes of a 177-year-old witch-that Sogolon had with the Aesi, chancellor to the king. It is said that Aesi works so closely with the king that together they are like the eight limbs of one spider. Aesi's power is considerable-and deadly. It takes brains and courage to challenge him, which Sogolon does for reasons of her own. Part adventure tale, part chronicle of an indomitable woman who bows to no man, it is a fascinating novel that explores power, personality, and the places where they overlap"--.
Keywords: Fantasy fiction; Science Fiction; Missing children; Courts and courtiers; Shapeshifting; Secrecy; Adventure stories; Historical fiction; Vendetta; Mercenary troops; Hunters; Truthfulness and falsehood; Epic fiction; Witches; Africa; Fantasy fiction